Modern faunistic variety of land vertebral landscapes of Stavropol plateau - Andrey Aleksandrovich Likhovid; Konstantin Viktorovich Kharin; Konstantin Yur’evich Shkarlet (Наука. Инновации. Технологии)
The current state of a faunistic variety of land vertebrata within landscapes of the Stavropol height is considered. The main types of biotopes of the animal population are revealed and the role of protected territories in preservation of modern fauna is shown.